Faktor-Faktor Yang Mempengaruhi Tingkat Pengetahuan Petani Tentang Program Peremajaan Kelapa Sawit Rakyat di Kecamatan Air Rami Kabupaten Mukomuko - Makayasa, Adhi; Andani, Apri; Yuliarso, M. Zulkarnain; Yuniarsih, Eka Triana (Jurnal MeA (Media Agribisnis), 2025)
Mukomuko Regency as established oil palm as the its economy ase, with a total plantation area of 102.66 thousand hectares 452.36 thousand tons of production in 2023. In Air Rami district however only 40% of productive oil palm area, while most of the plants are getting old and need replanting. However, many farmers have yet to undertake replanting due to limited knowledge and understanding, as well as a lack of extension services related to this program. This study aims to analyze the level of farmers' knowledge about the smallholder oil palm replanting program and identify the factors influencing it. Respondents were determined by Accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that the level of knowledge of farmers about the Smallholder oil palm rep3lanting program as a whole was classified as less good with a percentage of 61.43%.The variables of age and farming experience have a significant influence on the level of farmers' knowledge regarding oil palm replanting